Money and Inflation Nexus in Bangladesh - Uddin, Md. Nezum; Uddin, Mohammed Jashim; Ahmmed, Monir (Asian Economic and Financial Review, 2019)
This paper studies the causality link between inflation and money supply in Bangladesh. Monthly data running from May 2010 to August 2018 are utilized. M1 and M2 money are the instruments of money supply with CPI the measure of inflation. Unit root test results indicate all variables are stationary at level one. Cointegration tests found a long-run relation between M2 money supply and CPI. As the coefficient value of RESM2 (-1) is -0.40 for the short-run dynamic model, there is a strong indication that any deviation of the consumer price index (CPI) adjusts to its long-run equilibrium concerning M2 money at the rate of 40 per cent per month. However, the error correction model for M2 is found to be superior to M1.